2019
DOI: 10.12928/joves.v2i1.727
|View full text |Cite
|
Sign up to set email alerts
|

Resource Adequacy and Utilization for Teaching and Learning Effectiveness in Vocational Education Programmes in South-South Nigerian Universities

Abstract: This study investigated the level of physical facilities adequacy and instructional resources utilization for teaching and learning effectiveness in Technical and Vocational Education and Training (TVET) programmes. A quantitative research design was used, with a sample of 700 participants (85 lecturers and 615 students) which was randomly selected across three Federal Universities in South-South, Nigeria. Structured questionnaires were used to collect data from TVET lecturers and students. Mean, standard devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Hoy (2016) found the climate of the organization that produces the effective innovation process resulting from the institutional environment is safe, beautiful, and has enough space to learn as well as the provision of adequate facilities for the development of students," learning and instructors. According to Edokpolor & Dumbiri (2019), leaders in TVET institutions need to work in partnership with stakeholders to create a more conducive teaching and learning environment. This factor is important because it influences the psychological and emotional well-being of, the instructors, students or supporting staff of an institution.…”
Section: Innovation Leadership In Tvetmentioning
confidence: 99%
“…Hoy (2016) found the climate of the organization that produces the effective innovation process resulting from the institutional environment is safe, beautiful, and has enough space to learn as well as the provision of adequate facilities for the development of students," learning and instructors. According to Edokpolor & Dumbiri (2019), leaders in TVET institutions need to work in partnership with stakeholders to create a more conducive teaching and learning environment. This factor is important because it influences the psychological and emotional well-being of, the instructors, students or supporting staff of an institution.…”
Section: Innovation Leadership In Tvetmentioning
confidence: 99%
“…CNC machine is an electro-mechanical device that uses computer programming inputs to operate machine shop tools. [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Okonjo-Iwuala, [12], opine that it has been well documented that Nigeria's higher institutions ITE inclusive lack the tools to give students the skills needed for employment especially in the area of CNC machine. The study of [13] observed that the physical facilities and instructional resources (CNC facilities) for effective teaching and learning processes in ITE are inadequately provided and rarely utilized. Researchers have also argued that the poor acquisition of skills and utilization of CNC machines in ITE programmes is as a result of some factors which includes poor awareness and poor infrastructure, inadequate manpower and training among other [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Edokpolor (2018) stipulated that business education students often exhibit low self-confidence and determination towards lifelong learning. Edokpolor and Dumbiri (2019) averred that the reason for the increasing rates of students' dropout could be linked to the low supply of human, financial and material resources, which seem to have hindered the acquisition of 21st century skills required to be capable of taking part in entrepreneurial and lifelong learning activities immediately after graduation. These situations have become a treat to apparently all stakeholders in the country.…”
Section: Introductionmentioning
confidence: 99%